2017
DOI: 10.1111/cdep.12222
|View full text |Cite
|
Sign up to set email alerts
|

Callous–Unemotional Behaviors in Early Childhood: Measurement, Meaning, and the Influence of Parenting

Abstract: Antisocial behavior is costly and harmful to families, communities, and society. With roots in early childhood, antisocial behavior puts children at risk for poor physical and mental health outcomes across development. Callous-unemotional (CU) traits identify a subgroup of youth with particularly severe and stable antisocial behavior. While much literature has examined CU traits in late childhood and adolescence, researchers are just beginning to elucidate the developmental origins of CU traits. In this articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
39
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 61 publications
6
39
0
4
Order By: Relevance
“…Importantly, children with CU traits are unique in showing intact ToM despite deficits in emotion understanding or sensitivity (Dadds et al., ; Waller et al., ). Thus, emotion understanding represents a developmental marker and potential intervention target to ameliorate harmful pathways to CU traits and more severe forms of aggression (Waller & Hyde, ). Further work is needed to better understand ToM in children with CU traits in order to better tailor early interventions to their specific socioemotional skills and understandings of themselves and the people around them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, children with CU traits are unique in showing intact ToM despite deficits in emotion understanding or sensitivity (Dadds et al., ; Waller et al., ). Thus, emotion understanding represents a developmental marker and potential intervention target to ameliorate harmful pathways to CU traits and more severe forms of aggression (Waller & Hyde, ). Further work is needed to better understand ToM in children with CU traits in order to better tailor early interventions to their specific socioemotional skills and understandings of themselves and the people around them.…”
Section: Discussionmentioning
confidence: 99%
“…CU traits are defined by a lack of empathy or guilt, uncaring about school work or other important activities, and reduced emotional responsivity to others (Frick, Ray, Thornton, & Kahn, ). CU traits can be reliably measured in children as young 3 years old (for recent reviews, see Waller & Hyde, , ). Importantly, the presence of CU traits robustly predicts risk for more severe forms of aggression and rule‐breaking across childhood (Frick et al., ), making CU traits a critical target of investigation for reducing these harmful outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Individual differences in empathy-related responding emerge early in the second year of life, remain moderately stable across early childhood, and account for variability in children's social behavior and adjustment [Knafo et al, 2008;ZahnWaxler et al, 1992]. Children demonstrating callous-unemotional tendencies, including low levels of emotional arousal and empathic concern, have been identified as early as 3 years of age [Waller & Hyde, 2017]. Conversely, the tendency to experience overaroused and unregulated empathic responses (i.e., personal distress), which is common in the first few years of life, also persists in some individuals across the life span [Batson, 1991;Murphy, Eisenberg, Fabes, Shepard, & Guthrie, 1999].…”
Section: Individual Differencesmentioning
confidence: 99%
“…Research has identified several characteristic features of children showing CU traits, including more persistent and severe behavior problems, poor response to intervention, insensitivity to punishment cues, and atypical processing of emotional displays of distress [3,6,7]. The current study focuses specifically on this latter feature.…”
mentioning
confidence: 96%